Legitimação fundiária: a natureza jurídica e a constitucionalidade do modo originário de aquisição de propriedade criado pela Lei n. 13.465/2017 - Arthur Bittar Rodrigues Nunes (2023)
This paper aims to study the land legitimation, which is the mode of original acquisition of property conferred by act of public power, created by Law No.13,465/2017. Due to the incipient nature of land legitimation, there are few pacific positions about it, so there is no consensus on its constitutionality. Despite the creation of an institute hitherto foreign to the Brazilian legal system, its study by the investigated doctrine was mainly through comparative analysis with other forms of original acquisition of property, especially adverse possession and expropriation. From this comparative judgment, the doctrine has been presenting different conclusions about the legal nature of land legitimation, as well as its (in)constitutionality in the various cases of application, in view of its incidence in both public and private properties. In view of the multiplicity of understandings presented, we sought to analyze, also based on the comparison with adverse possession and expropriation, which are the points of contact and distance between the institutes, in order to reach the limits established in the Brazilian legal system about the disturbance in the right to real property.